Impact of permanent traffic lanes on the soil physical and mechanical properties in mechanized sugarcane fields with the use of automatic steering - Esteban, Diego Alexander Aguilera; de Souza, Zigomar Menezes; da Silva, Reginaldo Barboza [UNESP]; de Souza Lima, Elizeu; Lovera, Lenon Henrique; de Oliveira, Ingrid Nehmi (Elsevier, 2020)
The randomized traffic during all crop cycles in the Brazilian sugarcane production system enhances soil compaction. The use of automatic steering in controlled traffic farming represents an alternative to minimize soil compaction in the sugarcane fields. Our research aimed to evaluate the changes in the soil physical and mechanical properties under permanent traffic lanes, after three years of sugarcane mechanized harvesting, with the use of automatic steering. The experiment was carried out in the municipality of Nova Europa, state of São Paulo, Brazil, in a sugarcane area, under the following treatments: sugarcane planted in a single-row spacing (1.5 m) with conventional traffic, sugarcane planted in a single-row spacing (1.5 m) with automatic steering, and sugarcane planted with double-combined row spacing (1.50 × 0.90 m) and with automatic steering). The bulk density, soil porosity, soil penetration resistance, aggregate stability, and tensile strength of aggregates, were assessed in the inter-row center and seedbed. Soil load-bearing capacity was also included in this study by modeling of preconsolidation pressure at 0–0.1 m and 0.2–0.3 m of depth. After three years of mechanized operations, with controlled traffic using automatic steering, in a sugarcane field, the soil compaction was higher on the inter-row center (i.e. higher bulk density, tensile strength, and preconsolidation pressure and, lower macroporosity) than on the seedbed. The load-bearing capacity allowed to detect the pronounced effect of the machines’ traffic management systems on the soil compaction. The use of automatic steering reduced the load-bearing capacity in the seedbed in relation to the inter-row center, indicating that such management system preserves the soil physical quality in the ratoon region. Moreover, the lowest soil compression index values observed in the inter-row center, using management systems with automatic steering, indicates a lower susceptibility to undergo additional soil compaction.
Keywords: Controlled traffic; Preconsolidation pressure; Soil compaction; Soil friability; Tensile strength